Metabolic, transcriptomic, and genetic analyses of candidate genes for seed size in watermelon - Wang, Xiqing; Yan, Wen; Real, Núria; Jia, Yunhe; Fu, Yongkai; Zhang, Xuejun; You, Haibo; Cai, Yi; Liu, Bin (Frontiers in Plant Science, 2024)
Seed size (SS) constitutes a pivotal trait in watermelon breeding. In this study, we present findings from an examination of two watermelon accessions, namely, BW85 and F211. Seeds from BW85 exhibited a significant enlargement compared to those of F211 at 13 days after pollination (DAP), with the maximal disparity in seed length and width manifesting at 17 DAP. A comprehensive study involving both metabolic and transcriptomic analyses indicated a significant enrichment of the ubiquinone and other terpenoid-quinone biosynthesis KEGG pathways. To detect the genetic region governing seed size, a BSA-seq analysis was conducted utilizing the F2 (BW85 × F211) population, which resulted in the identification of two adjacent QTLs, namely, SS6.1 and SS6.2, located on chromosomes 6. SS6.1 spanned from Chr06:4847169 to Chr06:5163486, encompassing 33 genes, while SS6.2 ranged from Chr06:5379337 to Chr06:5419136, which included only one gene. Among these genes, 11 exhibited a significant differential expression between BW85 and F211 according to transcriptomic analysis. Notably, three genes (Cla97C06G113960, Cla97C06G114180, and Cla97C06G114000) presented a differential expression at both 13 and 17 DAP. Through annotation, Cla97C06G113960 was identified as a ubiquitin-conjugating enzyme E2, playing a role in the ubiquitin pathway that mediates seed size control. Taken together, our results provide a novel candidate gene influencing the seed size in watermelon, shedding light on the mechanism underlying seed development.